Former Yugoslav Republic of Macedonia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
The Macedonian labor market exhibits a high unemployment rate, yet does not demonstrate obvious and large enough constraints on the demand or supply side. Considerable achievements can be made by maintaining macroeconomic stability, attracting FDI, and closing the educational gaps. The second paper assesses ways in which the Macedonian financial sector could better contribute to growth and real convergence, taking stock of where the sector stands and its recent developments. Streamlining bankruptcy procedures, improving collateral and systematic collection and publication of real estate sales data, and revisiting the interest rate cap may serve to moderately boost credit supply.